The Effects of Water to Cement Ratio on Polyurethane Concrete Towards SDG Goals - muhammad zarul adham azmi; hasnida harun (Progress in Engineering Application and Technology, 2026)
The growing demand for sustainable and lightweight construction materials by investigating the optimization of the water-to-cement (w/c) ratio in polyurethane lightweight concrete (PU-LWC). The study examines the effects of different w/c ratios on the mechanical, physical, and durability properties of PU-LWC, aiming to enhance its performance for non-structural applications. Laboratory testing of PU-LWC samples with two w/c ratios (0.60 and 0.70), incorporating epoxy moulding compound (EMC) as a filler, reveals significant insights into the material’s compressive strength, density, and water absorption. The results demonstrate that a higher w/c ratio improves early-stage strength and enhances polymer dispersion but also increases porosity and water absorption. The study concludes that a w/c ratio of 0.70 provides an optimal balance between strength and lightweight characteristics, making it a promising material for sustainable construction practices.